A cloud broker architecture for cloud service selection based on multi-criteria decision making and rough set theory. (7th May 2020) - Talbi, Jamal; Haqiq, Abdelkrim
Cloud computing is a rising field providing computation resources. It represents a new paradigm of utility computing and enormously growing phenomenon in the present IT industry and economy hype. The companies which provide services to customers are called as cloud service providers. The cloud users (CUs) increase and require secure, reliable and trustworthy cloud service providers (CSPs) from the market. So, it's a challenge for a new user to choose the best provider. In this paper, we propose cloud broker architecture to help a new customer to find out the best CP. This architecture is based on a combination of rough set theory and multi-criteria analysis of some parameters related to the quality of service of the available providers. A mathematical model is used to do this analysis; it integrates multi-agent systems to present an intelligent, distributed and collaborative method in order to add assistance to each actor in cloud computing environment.